Transverse-Sigmoid Colon Synchronous Volvulus in a Patient with Lennox-Gastaut Syndrome: Case Report - Falcón-Cancino, Luis Arturo; Cruz-Mendez, Adriana Teresa; García-Flores, Rubén; Flores-López, Alejandro Alberto; Carrillo-Pinto, Laura Daniela Caridad; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: Lennox-Gastaut syndrome (LSG) is an epileptic encephalopathy characterized by a triad: 1). tonic seizures during sleep with atonic and atypical absence seizures, 2). cognitive and 3). behavioral It is estimated that SLG affects between 1 to 2% of patients with epilepsy. In general, LGS often occurs in young children. The etiology of LGS can be classified as cryptogenic or symptomatic. Symptomatic etiology of LGS can be secondary to hypoxic ischemic encephalopathy, congenital brain malformation, vascular malformation, genetics (tuberous sclerosis), trauma, brain tumor, or perinatal meningoencephalitis. Clinical Case: This is a 29-year-old woman, who has a significant history of prolonged prostration; severe cognitive disorder, Lennox-Gastaut syndrome since childhood. She was admitted to the emergency department with symptoms of abdominal distension of seven days of evolution and generalized pain in all abdominal quadrants. A simple computed tomography of the abdomen was performed, where distension of bowel loops was observed at the expense of mesenteric torsion with data of colonic volvulus with little free fluid. It is evaluated by the general surgery service who determines emergency surgical management by means of exploratory laparotomy, the following findings are addressed and obtained: toxic megacolon from the left end of the transverse colon to the middle third of the sigmoid colon, with multiple necrotic patches, as well as volvulus of the transverse and sigmoid colon, proceeding to perform a left hemicolectomy with colostomy of the transverse colon. Discussion: In children, the incidence is estimated at 2 per 100,000, and it is common in men. LGS is one of the most commonly encountered drug-resistant epileptic encephalopathies, with mortality rates ranging from 3-7%. There are many treatment options for these patients, such as antiepileptic drugs, ketogenic diets, VNS therapy (vagus nerve stimulation) callosotomy, and resective epilepsy surgery.